2021
DOI: 10.3390/su13105677
|View full text |Cite
|
Sign up to set email alerts
|

The Livelihoods Impacts of Irrigation in Western Africa: The Ghana Experience

Abstract: Although agriculture remains the mainstay of the African economy, it is currently going through stress because of a multitude of factors including climate change. Thus, many countries in their efforts to transform their agricultural sectors are employing climate-smart initiatives including the provision of water harvesting technologies for irrigated crop production during the dry season. This paper examines the role of irrigation in the drive towards a transformation of smallholder agriculture in Africa. Focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…There is evidence which suggests that irrigation contributes to household food security [ [31] , [32] , [33] , [34] ], livelihoods of the rural poor [ [35] , [36] , [37] , [38] ], agricultural intensification and productivity [ [39] , [40] , [41] , [42] , [43] , [44] ], and poverty reduction [ 9 , 26 , [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. Among other factors like type of system, availability of water resources, soil fertility, access to credit and markets, the socio-economic impact of smallholder irrigation largely determines the success and sustainability of the project [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence which suggests that irrigation contributes to household food security [ [31] , [32] , [33] , [34] ], livelihoods of the rural poor [ [35] , [36] , [37] , [38] ], agricultural intensification and productivity [ [39] , [40] , [41] , [42] , [43] , [44] ], and poverty reduction [ 9 , 26 , [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. Among other factors like type of system, availability of water resources, soil fertility, access to credit and markets, the socio-economic impact of smallholder irrigation largely determines the success and sustainability of the project [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of smallholder irrigation to farmers’ livelihoods has also been an area of interest to researchers. It is often argued that smallholder irrigation can be a basis for rural development and improved livelihoods in rural poor communities [ 35 , 36 , 38 ]. Four studies were included in the review to assess the contribution of smallholder irrigation to livelihoods (see Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Akudugu [6] revealed that the immediate and direct impact of irrigation on livelihoods farmers in the community were involved in irrigated agriculture, the average farm income would have been about GHS 1881.80 (USD 493.91) and this was found to be significant at 1%. With the presence of irrigation facilities across the communities, the average farm income is about GHS 2717.62 (USD 713.29) and this was found to be statistically significant at 1%.…”
Section: Original Research Articlementioning
confidence: 99%